Removal of waterborne phage and NO3− in the nZVI/phage/NO3− system: competition effect. Issue 41 (11th May 2017) - Cheng, Rong; Xue, Xing-yan; Li, Guan-qing; Shi, Lei; Kang, Mi; Zhang, Tao; Liu, Ya-ping; Zheng, Xiang; Wang, Jian-long
Abstract : There was competition between phage f2 and NO3 − to react with nZVI, and the interaction was affected by nZVI dosage and pH. Abstract : Waterborne pathogenic viruses are a threat to public health. Nanoscale zero-valent iron (nZVI) has increasingly been applied to the removal of viruses. However, current studies are usually based on single component systems, which are not consistent with reclaimed water containing various pollutants in complex mixtures. In this study, a coexisting system containing microorganisms and chemical substances was constructed. Phage f2 and NO3 − were selected as the model virus and nutrient substance in water to investigate the removal of waterborne phage and a chemical substance in an nZVI/phage/NO3 − system. The results showed that phage f2 and NO3 − could coexist without interference in a phage/NO3 − system, while there was competition between phage f2 and NO3 − for nZVI when nZVI was added. The removal efficiency of phage f2 decreased with an increase in NO3 − concentration (0–100 mg L −1 ). When the initial concentration of virus was 8 × 10 5 PFU mL −1, the virus removal efficiency was not altered by NO3 − ; however, it was significantly reduced by NO3 − when the initial concentration of the virus was increased (8 × 10 6 to 8 × 10 7 PFU mL −1 ). In addition, the virus (8 × 10 6 PFU mL −1 ) reduced the NO3 − (20 mg L −1 ) removal by nZVI (60 mg L −1 ). With an increase in nZVI dosage, the virus removal efficiency first increased and then decreased irrespective of NO3 − being present. Nevertheless, the turning point of virus removal efficiency was retard in the presence of NO3 − . The removal efficiency of NO3 − increased with an increase in the nZVI dosage (20–120 mg L −1 ) irrespective of whether the virus was present, but the effect of virus on NO3 − removal was weakened. Under acidic conditions, phage f2 was superior to NO3 − in reacting with nZVI, and NO3 − was superior to phage f2 under alkaline conditions.